2018
DOI: 10.1002/uog.18953
|View full text |Cite
|
Sign up to set email alerts
|

PRospective Imaging of CErvical cancer and neoadjuvant treatment (PRICE) study: role of ultrasound to assess residual tumor in locally advanced cervical cancer patients undergoing chemoradiation and radical surgery

Abstract: Our results show that grayscale and color Doppler ultrasound have a low level of diagnostic performance in detecting residual disease after neoadjuvant chemoradiation in patients with locally advanced cervical cancer. The best performance was achieved in detection of macroscopic (≥ 6 mm) residual disease. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A total of 254 locally advanced cervical cancer patients (FIGO 2018 stages IB2–IVA)14 treated with chemoradiotherapy followed by radical surgery, between January 2004 and March 2018, were included. Data for these patients were retrieved from our four phase II clinical studies15–18 based on preoperative chemoradiotherapy followed by surgery; this approach, which replaces intracavitary vaginal brachytherapy with surgery after chemoradiotherapy, has been proposed to improve local disease control and reduce radiation dose and potential toxicity 13. Two meta-analyses published by Shim et al19 and Lu et al20 reported that completion hysterectomy after chemoradiotherapy versus exclusive chemoradiotherapy did not improve survival in locally advanced cervical cancer patients, but seemed to reduce the risk of local recurrence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 254 locally advanced cervical cancer patients (FIGO 2018 stages IB2–IVA)14 treated with chemoradiotherapy followed by radical surgery, between January 2004 and March 2018, were included. Data for these patients were retrieved from our four phase II clinical studies15–18 based on preoperative chemoradiotherapy followed by surgery; this approach, which replaces intracavitary vaginal brachytherapy with surgery after chemoradiotherapy, has been proposed to improve local disease control and reduce radiation dose and potential toxicity 13. Two meta-analyses published by Shim et al19 and Lu et al20 reported that completion hysterectomy after chemoradiotherapy versus exclusive chemoradiotherapy did not improve survival in locally advanced cervical cancer patients, but seemed to reduce the risk of local recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…Pelvic ultrasound was used, but not as staging. Preoperative chemoradiotherapy was administered as whole pelvic irradiation (total dose 39.6–50.4 Gy) with cisplatin-based regimens 15–18…”
Section: Methodsmentioning
confidence: 99%
“…For each session, the planned time interval between the three imaging modalities did not exceed 1 week. In the present study, we considered ultrasound data only, obtained at baseline and after 2 weeks of treatment, while the ultrasound data from the final evaluation and the data for the other two diagnostic methods, MRI and PET/CT, will be presented in further papers, including only the best ultrasound variables identified by the present analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Research on 3D US and cervical cancer has focused as well on the possible predictive value for patients that are subject to NACT before surgery or primary RCT with negative results. FI was suggested as a predictive marker for NACT responders, (129) however, neither in the prospective PRICE study nor another smaller study were 3D vascular indices found useful to monitor response to NACT or RCT in patients with advanced disease (121,130).…”
Section: Three Dimensional Ultrasonography (3d)mentioning
confidence: 99%